A Comparison Of Crassostrea gigas And Crassostrea virginica: Effects Of Temperature And Salinity On Susceptibility To The Protozoan Parasite, Perkinsus marinus - Chu, Fu-Lin C.; Volety, Aswani; Constantin, G (W&M ScholarWorks, 1996)
The susceptibility of diploid and triploid (2N and 3N) Crassostrea gigas to Perkinsus marinus was compared, in the laboratory, with that of Crassostrea virginica al three test temperatures (10, 15, and 25 degrees C) at 20-22 ppt and at three test salinities (3, 10, and 20 ppt) at a temperature of 19-22 degrees C. Experimental oysters were challenged twice with freshly isolated P, marinus meronts, after acclimation to test temperatures and salinities. Although infection prevalence and intensity increased with temperature (p = 0.0001) and salinity in P. marinus-challenged oysters of both oyster species: they were highest in C. virginica groups. Infection intensity was significantly (p = 0.001) higher in P. marinus-challenged C. virginica than C. gigas (2N and 3N) at all temperatures; however, infection prevalence was not statistically different at any temperature treatment. In all salinity treatments, prevalence and infection intensity were significantly higher (p = 0.0001) in P. marinus-challenged C. virginica than 2N and 3N C. gigas. Because high infection prevalence and intensity were found in non-challenged C. virginica, part of the recorded prevalence and intensity in challenged C. virginica was probably attributed to latent infection carried over from the field. High mortality occurred in both 2N and 3N C. gigas during temperature and salinity adjustment, particularly at 25 degrees C and 3 psu.